High Performance Computing in Science and Engineering’ 05: Transactions of the High Performance Computing Center Stuttgart (HLRS) 2005 - Nagel, Wolfgang E.; Resch, Michael; Jäger, Willi (Springer-Verlag Berlin Heidelberg, 2006)
Physics -- Simulations of Astrophysical Jets in Dense Environments -- Numerical Simulations of Host Galaxies of Gamma-Ray Bursts -- Electron-doping Evolution of the Quasiparticle Band of the Cuprates -- Libraries and Methods for Parallel Particle Simulations -- Solid State Physics -- Numerical Simulations of Quantum Gases, Magnetic, and Correlated Electronic Systems -- Large-Scale Simulations for Understanding Surface Optical Spectra -- Numerical Investigations of Nano-Systems in Reduced Geometry -- Computational Fluid Dynamics -- Direct Numerical Simulation of Non-Linear Transitional Stages in an Experimentally Investigated Laminar Separation Bubble -- Instabilities in Hypersonic Boundary Layers Under the Influence of High-temperature Gas Effects -- Direct Numerical Simulation of Breakup Phenomena in Liquid Jets and of Colliding Raindrops -- Numerical Investigation of the VKI Turbine Blade by Large Eddy Simulation -- A Hybrid LES/CAA Method for Aeroacoustic Applications -- Using Dynamic Mesh Models to Simulate Electrostatic Spray-Painting -- Numerical Simulation of Maneuvering Combat Aircraft -- Advanced Rotary Wing Aeromechanics -- Time-Accurate versus Actuator Disk Simulations of Complete Helicopters -- LES of Shock Wave/Turbulent Boundary Layer Interaction -- Detailed Combustion and Steamside Simulation of Fossil-fuel Fired Utility Boilers -- Chemistry -- Computational Chemistry -- Quantum Mechanical Studies of Boron Clustering in Silicon -- Ionic Liquids from A1C13 -- Miscellaneous Topics -- Considerations of the Biot Velocity Relations: Viscous Finite-difference Calculations in Combination with Flow Simulations -- Plateness of the Oceanic Lithosphere and the Thermal Evolution of the Earth’s Mantle -- Use of High Performance Computing in Gravity Field Research -- Molecular Modeling of Hydrogen Bonding Fluids -- Benchmarking MPI One-sided Communication with SKaMPI-5.
Includes bibliographical references
Keywords: Aufsatzsammlung; Technik; Hochleistungsrechnen; Naturwissenschaften